1987
DOI: 10.1128/aac.31.8.1263
|View full text |Cite
|
Sign up to set email alerts
|

Failure of effervescent zinc acetate lozenges to alter the course of upper respiratory tract infections in Australian adults

Abstract: Effervescent lozenges containing 10 mg of zinc acetate were evaluated as a treatment of upper respiratory tract infections in a double-blind randomized trial by using a placebo which was indistinguishable to most observers in taste and appearance from the active material. Of the 70 treatment courses used by 55 individuals in 34 families, 63 (33 zinc and 30 placebo) were considered evaluable, in that the volunteer used the medication at least four times daily for at least 3 days, the average utilization being 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 5 publications
0
72
0
Order By: Relevance
“…In the literature quoting mean duration of a common cold, 3,[14][15][16][17] it has been specified that the cold is considered to have begun when one or more symptoms are present for 2 days, or two symptoms are present for 1 day. In the present study, the onset of the cold was defined a s t he ti me wh e n t he f ir st sy mpt om wa s recognized by the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature quoting mean duration of a common cold, 3,[14][15][16][17] it has been specified that the cold is considered to have begun when one or more symptoms are present for 2 days, or two symptoms are present for 1 day. In the present study, the onset of the cold was defined a s t he ti me wh e n t he f ir st sy mpt om wa s recognized by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts made to duplicate the success which Eby et al 1 had in 1984 in reducing the duration of the common cold using zinc gluconate have generally been disappointing, [2][3][4] the probable reason being that zinc gluconate was inactivated by additives used to mask its unpleasant taste. It has been demonstrated that of these agents, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no reduction in the rate or amount ofvirus shedding occurred. The results of further studies suggested that no beneficial effect resulted from the use of either zinc acetate or zinc gluconate Douglas et al, 1987;Geist et al, 1987). In addition, the results of a study involving the ingestion ofzinc where subjects ingested 300 mg day-l for 6 weeks indicated that there was a significant reduction in lymphocyte proliferative responses, polymorphonuclear phagocytic function and high-density lipoprotein concentrations (Chandra, 1984).…”
Section: Zinc Saltsmentioning
confidence: 90%
“…Nasal mucous weights and number of tissues used were higher in subjects taking zinc gluconate. Douglas et al (2) used effervescent zinc acetate lozenges in subjects with naturally acquired URIs. There were no differences in effect on severity or duration of symptoms between zinc and placebo recipients.…”
Section: Discussionmentioning
confidence: 99%